Was Dewey (Too) Modern? The Modern Faces of Dewey - Zrudlo, Ilya (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2021)
Although John Dewey continues to be a source to which scholars look in order to address contemporary social and educational issues, others have suggested that Dewey may be too implicated in the project of modernity to be acceptable in educational theory and practice today. To what extent Dewey was modern, and what we make of the question of his modernity, depends on our reading of Dewey and on our understanding of modernity more generally. I will argue that a broad reading of both Dewey and modernity helps us avoid treating Dewey either as education’s saviour or as inimical to our present purposes. First, I examine Dewey’s own conception of modernity and then broaden its scope by bringing into view four aspects of Western modernity: economic modernization, the struggle for justice, individualism, and naturalism. Second, I show how Dewey can and has been read as representing one or more of these aspects, but also from the perspective of one or more of these aspects. This generates what I will call Dewey’s four “faces”: Dewey as engineer, Dewey as activist, Dewey as Romantic, and Dewey as naturalist. This mapping offers a way of making more sense of the diverse readings of Dewey that exist in the secondary literature. Finally, I make a case for Dewey’s ongoing relevance because of his capacious view of the goods of modernity and his distinctively educational philosophy.